Single-cell analyses reveal the therapeutic effects of ATHENA and its mechanism in a rhabdomyosarcoma patient - Liu, Yujun; Wang, Ke; Zhou, Yanli; Zhuang, Xibing; Shao, Shali; Qiao, Fulu; Wang, Xiangdong; Zou, Xin; Qiao, Tiankui (Frontiers in Oncology, 2022)
Background Whole-cell tumor vaccines tend to suffer from low immunogenicity. Our previous study showed that irradiated lung cancer cell vaccines in mouse models enhance antitumor efficacy by eliciting an intensive T cells response and improving immunogenicity. Based on these findings, we developed an improved whole-cell tumor vaccine, Autologous Tumor Holo antigEn immuNe Activation (ATHENA). Methods In this study, we report the successful treatment of a 6-year-old male diagnosed with meningeal rhabdomyosarcoma with pulmonary and liver metastases using ATHENA. After 6 cycles of therapy, PET/CT showed the therapeutic efficacy of ATHENA. We profiled the immune response by single-cell RNA sequencing (scRNA-seq). Flow cytometry analysis was implemented to validate the status transitions of CD8+ T cells. Results In CD8+ T cells, the exhausted status was weakened after treatment. The exhausted CD4+ T cells shifted towards the central memory phenotype after the treatment. Breg cells were converted to Plasma or Follicular B cells. Survival analysis for pan-cancer and transcription factor analysis indicated that such T cell and B cell transitions represent the recovery of antitumoral adaptive immune response. We validated that the proportion of CD279+CD8+ T cells were reduced and the expression of CD44 molecule was upregulated by flow cytometry assay. Conclusion Such studies not only show that ATHENA therapy may be a promising alternative treatment for tumor patients but provide a novel idea to analyses the mechanisms of rare cases or personalized cancer treatment.